Use of Online Medical Databases by Medical Professionals in Bangalore City - John, S.; Gandhi, Ramesh (Journal of Information and Knowledge, 2012)
Biomedical scholars are increasingly turning to electronic databases to find information. No database can contain all the available information. Thus each database has its own limitations. Therefore, some may be asking, "Do I have the right database to find what I need and if not, where is the right database to be found?" There are dozens of health science databases provided by the National Library of Medicine, and from some commercial publishers like Cochrane Collaboration, OVIDSP, and EBSCO, hundreds of more databases from other vendors. Also there are Online Databases having full text links (such as AIDSDRUGS, CANCERLIT, PUBMED CENTRAL, SCIENCE DIRECT, MD CONSULT, GOOGLE SCHOLAR) etc. It is found that database for the requirement of information is the best strategy, which depends on awareness of the users about the databases where librarian have to take responsibility of creating awareness and training users.